The digitalisation in chartering business: Special reference to the role of e-bill of lading in the bulk and liner markets - Evi Plomaritou; Sotiris Jeropoulos (Journal of Shipping and Trade (JST), 2022)
Previous research offering a comprehensive overview of digitalisation in maritime transport is limited. In this paper, the authors use several cases to examine digitalisation's role in the chartering business. The applications of innovative digitalisation to enhance efficiency in the shipping business are presented analytically. Special emphasis is given to the role of the e-bill of lading in the bulk and liner markets. The advantages, disadvantages and legal barriers of the e-bill of lading are examined thoroughly for both markets (bulk and liner markets). The research follows a qualitative case study approach. It shows that although digital technologies offer important advantages in the chartering business, many legal barriers still need to be overcome. The findings fill the gap in the literature and assist maritime professionals and shipping companies in understanding the necessity of digitalisation in chartering business.
Keywords: 650; Chartering business; Digitalisation; E-bill of lading; Charter party; Chartering negotiation; Pre-fixture; Post-fixture; Fixture